Manajemen Media Dalam Pembentukan Opini Publik oleh Satuan Kerja Bidang Hubungan Masyarakat Kepolisian Daerah Sumatera Barat: Kasus Tewasnya Afif Maulana Tahun 2024 - Agrisukma, Gayuh; Wahyurudhanto, Albertus (Brand Communication, 2025)
This study aims to analyze the public relations management strategies implemented by the West Sumatra Regional Police Public Relations Work Unit in addressing media coverage concerning the death of Afif Maulana. This research is grounded Timothy Coombs' Situational Crisis Communication Theory (SCCT), which emphasizes the importance of situational- based communication in crisis management. The study employs a qualitative approach using a case study method. Data was collected through document analysis and observations of media reports and public responses. The findings indicate that the Public Relations Management Strategy of the West Sumatra Regional Police followed a Three-Staged Approach to crisis communication: (1) Pre-Crisis, triggered by media reports and the victim's family's response; (2) Crisis Event, marked by protests and the viral spread of the case on social media; (3) Post-Crisis, where the police closed the investigation, citing the cause of death as bodily impact against a hard object rather than abuse. Several factors influenced the inconsistency in public opinion: (1) Strengths, the role of social media and experts in disseminating information; (2) Weaknesses, unclear official investigations and biased media reports; (3) Opportunities, broader public access to diverse sources of information; (4) Threats, the spread of misinformation and interventions that undermined the credibility of the legal process. The Public Relations Division of the West Sumatra Regional Police has made efforts to shape public opinion and build public trust in line with Public Management concepts.